The Effect of Organizational Citizenship Behaviour (OCB) on Employee Performance with Work Overload as a Mediating Variable at PT Tuntun Sekuritas Indonesia - Reizha Nurul Huda; Habibullah Jimad; Ribhan (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to analyze the effect of Organizational Citizenship Behavior (OCB) on employee performance, with work overload as a mediating variable at PT Tuntun Sekuritas Indonesia. The study adopts a quantitative approach using a survey method. Data were collected through questionnaires distributed to employees of PT Tuntun Sekuritas Indonesia and analyzed using Structural Equation Modeling (SEM) with the assistance of AMOS software. The results of the analysis indicate that Organizational Citizenship Behavior (OCB) has a positive and significant effect on employee performance. However, based on the Sobel test results, work overload is not proven to mediate the relationship between OCB and employee performance. This finding suggests that the influence of OCB on employee performance occurs directly rather than through an increased workload mechanism. The results imply that employees’ extra-role behaviors play an important role in enhancing performance in securities companies. Nevertheless, organizations still need to manage workloads proportionally to ensure that OCB does not lead to long-term work fatigue. This study is expected to contribute theoretically to the development of organizational behavior literature and practically to serve as a consideration for management in human resource management.